Leptospirosis in pregnancy: a case report - Guleria, Sara; Dev, Kapil; Pathania, Kushla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Leptospirosis is a leading zoonotic disease worldwide with more than 1 million cases in the general population per year. There is significant mortality due to both delays in diagnosis as well as adequate clinical suspicion. There is also an overlap between the signs, symptoms and biochemical disturbances associated with leptospirosis in pregnancy and the presentation of pregnancy associated conditions, such as pre-eclampsia (PET), acute fatty liver of pregnancy (AFLP) and haemolysis elevated liver enzymes low platelets (HELLP) syndrome. This is a case report of a pregnant woman with leptospirosis who delivered a healthy fetus.